Identitas Kelompok Pecinta Mobil Daihatsu Ayla Palembang - Veven Mira Noverina; Dadang Hikmah Purnama; Faisal Nomaini (Jurnal Empirika, 2019)
This research discussed about â€œThe Identity Of Daihatsu Ayla Lovers in Palembangâ€. The problem of this research is the existence of Daihatsu Ayla lovers in Palembang which is in Low-Cost Green Car (LCGC) category that is different with other general carâ€™s lovely which have fancy and unique car represents identity as higher class and prestige. The method of research in verificative qualitative. Data collecting technics are observation, interview, and documentation. This research uses social identity theory by Tajfel and Turner. The result of the study is that Daihatsu Ayla lovers in Palembang manifested from the connection in sign, which showed by attributes or ornaments in their activities that contain the same valves so that it creates an in-group feeling as professional, loyal, and simple car lovers. This identity comes from the process in social identity creating, which begins with a social orientation of the member toward Daihatsu Ayla lovers in Palembang. Then, the second process is social identification, that is every member should adapt with the identity that has been categorised. The last method is a social comparison, where Daihatsu Ayla lovers do some comparison in group and out-group or Ayla Indonesia Club (CAI). Next, the identity which possessed by Daihatsu Ayla shows their identity as carâ€™s lovers which prefer family sense and low profile